ヒト免疫不全ウイルス感染者に生じた下唇扁平上皮癌の1例 - 重冨, 俊夫; 總山, 貴子; 萩野, 浩子; 宇佐美, 雄司; 荒川, 美貴子; 松浦, 由佳 (日本口腔外科学会雑誌, 2020)
Recent advances in anti-retroviral therapy (ART) have led to patients with HIV infection living longer. The frequency of non-AIDS-defining malignancies (NADM), including head and neck cancer, has increased. In this study, we report our experience with the treatment of lower lip carcinoma with HIV infection. The patient was a 64-year-old-man with HIV infection. He referred to our clinic because of a lower lip tumor. We performed biopsy, and the tumor was diagnosed as squamous cell carcinoma. He received chemotherapy followed by surgical operation, tracheostomy, functional neck dissection, lower lip carcinoma resection, and reconstruction of the tongue, with no severe events. There has been no recurrence or metastasis during about 2 years.